2017
DOI: 10.1002/chem.201703109
|View full text |Cite
|
Sign up to set email alerts
|

Tris(2,4,6‐trifluorophenyl)borane: An Efficient Hydroboration Catalyst

Abstract: The metal‐free catalyst tris(2,4,6‐trifluorophenyl)borane has demonstrated its extensive applications in the 1,2‐hydroboration of numerous unsaturated reagents, namely alkynes, aldehydes and imines, consisting of a wide array of electron‐withdrawing and donating functionalities. A range of over 50 borylated products are reported, with many reactions proceeding with low catalyst loading under ambient conditions. These pinacol boronate esters, in the case of aldehydes and imines, can be readily hydrolyzed to lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
54
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 114 publications
(59 citation statements)
references
References 28 publications
5
54
0
Order By: Relevance
“…All these procedures require more or less effective catalysts based on transition-metal complexes such as Co, Fe, Ru, [15][16][17][18][19][20][21][22][23] alkaline earth metal (Mg), [24][25][26][27][28][29][30][31][32][33][34][35] but the processes culminate in frustrated Lewis pairs. [36][37][38] On the other hand, while the reduction of aryl and alkyl nitriles can be achieved using stoichiometric quantities of maingroup reducing agents such as LiAlH 4 and NaBH 4 , [39] the combustible nature of these reagents and large quantities of inorganic waste by-products they generate render the process unattractive, and hence reductive hydroboration is preferable in order to provide further functionality to the resultant amine. [40] Recently, Nakazawa et al reported the use of an ironindium complex as a catalyst for the hydroboration of aryl and alkyl nitriles, [41] while Nikonov et al introduced the Mo(IV) complex as a catalyst (5 mol %), which resulted in the hydroboration of acetonitrile and benzonitrile using the only catecholborane.…”
Section: Introductionmentioning
confidence: 99%
“…All these procedures require more or less effective catalysts based on transition-metal complexes such as Co, Fe, Ru, [15][16][17][18][19][20][21][22][23] alkaline earth metal (Mg), [24][25][26][27][28][29][30][31][32][33][34][35] but the processes culminate in frustrated Lewis pairs. [36][37][38] On the other hand, while the reduction of aryl and alkyl nitriles can be achieved using stoichiometric quantities of maingroup reducing agents such as LiAlH 4 and NaBH 4 , [39] the combustible nature of these reagents and large quantities of inorganic waste by-products they generate render the process unattractive, and hence reductive hydroboration is preferable in order to provide further functionality to the resultant amine. [40] Recently, Nakazawa et al reported the use of an ironindium complex as a catalyst for the hydroboration of aryl and alkyl nitriles, [41] while Nikonov et al introduced the Mo(IV) complex as a catalyst (5 mol %), which resulted in the hydroboration of acetonitrile and benzonitrile using the only catecholborane.…”
Section: Introductionmentioning
confidence: 99%
“…2‐(4‐Fluorobenzyloxy)pinacolborane (1f): 1 H NMR (600 MHz, C 6 D 6 ): δ = 7.10–7.04 (m, 2H), 6.80–6.73 (m, 2H), 4.79 (s, 2H), 1.04 (s, 12H). 13 C{ 1 H} NMR (151 MHz, C 6 D 6 ): δ = 162.6 (d, 1 J CF = 244.6 Hz), 135.8 (d, 4 J CF = 3.3 Hz), 128.9 (d, 3 J CF = 8.0 Hz), 115.3 (d, 2 J CF = 21.4 Hz), 82.8, 66.2, 24.7.…”
Section: Methodsmentioning
confidence: 99%
“…2‐(2‐Bromobenzyloxy)pinacolborane (1i): 1 H NMR (600 MHz, C 6 D 6 ): δ = 7.54 (d, 3 J HH = 7.5 Hz, 1H), 7.26 (d, 3 J HH = 7.5 Hz, 1H), 6.96 (t, 3 J HH = 7.5 Hz, 1H), 6.70 (t, 3 J HH = 7.5 Hz, 1H), 5.09 (s, 2H), 1.04 (s, 12H). 13 C{ 1 H} NMR (151 MHz, C 6 D 6 ): δ = 139.0, 132.5, 128.8, 128.0, 127.6, 121.8, 83.0, 66.6, 24.7.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] Classically, there has been focus on the use of precious metal catalysts for this transformation, [4][5][6] but recently there has been a surge of interest in using more abundant, non-toxic, and cheaper alternatives such as early transition metals and main group elements. 1,[7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] Recent work has shown that Lewis acidic boranes and borocations can act as efficient catalysts for this process (Fig. 1).…”
mentioning
confidence: 99%